The Director’s Duty of Care: A Comparative Analysis of Delaware and Singapore Laws - Huan, Julie L.Y. (Columbia Journal of Asian Law, 1998)
In a typical corporation, the board of directors is charged with the function of managing the corporation’s business. The power to man age the corporation carries with it a duty to act in the best interest of the corporation. This translates into a duty to exercise care and to remain loyal to the corporation at all times. While the concept of a duty of care is universal, the degree of care expected of a director varies in different jurisdictions. This paper provides a comparative analysis of a director’s duty of care under the laws of the State of Delaware in the United States and the Republic of Singapore. The author first introduces the general principles developed under these two jurisdictions. Thereafter, both Delaware and Singapore laws are applied to fact scenarios taken from three Delaware cases to illustrate similarities and differences in the approaches adopted by the two jurisdictions. Finally, the author provides an overall comparative analysis and some recommendations for improvement to Singapore law.